The incorporation of cystine by the soluble carrier family 7 member 11 (SLC7A11) is a component of the redox regulatory mechanism in stallion spermatozoa†. Issue 1 (18th April 2019) - Ortiz-Rodriguez, José Manuel; Martín-Cano, Francisco E; Ortega-Ferrusola, Cristina; Masot, Javier; Redondo, Eloy; Gázquez, Antonio; Gil, María C; Aparicio, Inés M; Rojo-Domínguez, Patricia; Tapia, José A; Rodriguez-Martínez, Heriberto; Peña, Fernando J
Abstract: Oxidative stress is considered a major mechanism causing sperm damage during cryopreservation and storage, and underlies male factor infertility. Currently, oxidative stress is no longer believed to be caused only by the overproduction of reactive oxygen species, but rather by the deregulation of redox signaling and control mechanisms. With this concept in mind, here, we describe for the first time the presence of the soluble carrier family 7 member 11 (SLC7A11) antiporter, which exchanges extracellular cystine (Cyss) for intracellular glutamate, in stallion spermatozoa, as well as its impact on sperm function using the specific inhibitor sulfasalazine. Spermatozoa incubated with Cyss exhibited an increased intracellular GSH content compared with controls ( P  < 0.01): 50% in fresh extended stallion spermatozoa and 30% in frozen-thawed spermatozoa. This effect was prevented by the addition of sulfasalazine to the media. Cystine supplementation also reduced the oxidation–reduction potential of spermatozoa, with sulfasalazine only preventing this effect on fresh spermatozoa that were incubated for 3 h at 37°C, but not in frozen-thawed spermatozoa. While sulfasalazine reduced the motility of frozen-thawed spermatozoa, it increased motility in fresh samples. The present findings provide new and relevant data on the mechanism regulating the redox status of spermatozoa and suggest that a different redox regulatory mechanism exists in cryopreserved spermatozoa, thus providing new clues to improve current cryopreservation technologies and treat male factor infertility. Abstract : The SLC7A11 antiporter that exchanges cystine by intracellular glutamate is present and functional in stallion spermatozoa, but cryopreserved spermatozoa may present altered functionality.